A Longitudinal Study on Generalized Anxiety Among University Students During the First Wave of the COVID-19 Pandemic in Switzerland - Amendola, Simone; von Wyl, Agnes; Volken, Thomas; Zysset, Annina; Huber, Marion; Dratva, Julia (Frontiers in Psychology, 2021)
Objective: The COVID-19 pandemic and government measures implemented to counter the spread of the infection may be a major stressor affecting the psychological health of university students. This study aimed to explore how anxiety symptoms changed during the pandemic. Methods: 676 students (76% females) at Zurich University of Applied Sciences participated in the first (T0) and second (T1) survey waves. Anxiety symptoms were assessed using the Generalized Anxiety Disorder-Scale-7 (GAD-7). Risk and protective factors (e.g., COVID-19-related variables) were examined. Results: GAD-7 scores decreased significantly from T0 to T1 (mean change: -0.446, SE = 0.132, 95% CI: -0.706, -0.186, t = -3.371, df = 659, p = 0.001). Participants with moderate-to-severe anxiety score were 20.2% and 15.6% at T0 and T1, respectively. The following positively predicted anxiety: older age, female gender, non-Swiss nationality, loneliness, participants' concern about their own health, and interaction between time and participants' concern about their own health. Resilience and social support negatively predicted anxiety. Conclusions: Our findings provide information for public health measures and psychological interventions supporting the mental health of university students during the COVID-19 emergency.